Voxel-Wise Analysis of Structural and Functional MRI for Lateralization of Handedness in College Students - Wang, Haha; Zhou, Hong; Guo, Yihao; Gao, Lei; Xu, Haibo (Frontiers in Human Neuroscience, 2021)
The brain structural and functional basis of lateralization in handedness is largely unclear. Our study aimed to explore this issue by using voxel-mirrored homotopic connectivity (VMHC) measured by Resting-state functional magnetic resonance imaging (R-fMRI) and gray matter asymmetry index (AI) by high-resolution anatomical images. A total of fifty healthy subjects were included, among them were 13 left-handers, 24 right-handers and 13 mixed-handers. Structural and resting-state functional MRI of all subjects were collected. There were significant differences in VMHC among the three groups in lateral temporal-occipital, orbitofrontal and primary hand motor regions. Meanwhile, there were significant differences in AI that existing in medial prefrontal, superior frontal, and superior temporal regions. Besides, the correlation analysis showed that the closer the handedness score to the extreme of the left-handedness, the stronger interhemispheric functional connectivity，as well as more leftward grey matter. In general, left/mixed-handedness showed stronger functional homotopy in the transmodal association regions that depend on the integrity of the corpus callosum, but more variable in primary sensorimotor cortices. Furthermore, the group differences in VMHC largely align with that in AI. We located the specific regions for left/mixed-handedness from the perspective of structural and functional specification, suggesting the plasticity of hand movement and different patterns of emotional processing. Key words: handedness; voxel-mirrored homotopic connectivity; asymmetry index; magnetic resonance imaging